Acerentulus tortii sp. nov. from Greece (Protura: Acerentomidae) - Galli, Loris; Capurro, Matteo; Lionetti, Giuseppe; Zinni, Matteo (Zootaxa, 2017)
A new species of Protura, Acerentulus tortii sp. nov., from the island of Euboea, central Greece, is described and illustrated. The new species belongs to the A. cunhai species group, based on a short foretarsal sensillum a not reaching seta γ3, and sensilla b and c subequal in length. The most similar species are A. christensoni (Ewing, 1940) and A. rafalskii Szeptycki, 1979), from which A. tortii sp. nov. differs by the porotaxy of sternite III and the lengths of various foretarsal sensilla.